2022
DOI: 10.3390/healthcare10030439
|View full text |Cite
|
Sign up to set email alerts
|

Association between Frequency of Going Out and Psychological Condition among Community-Dwelling Older Adults after the COVID-19 Pandemic in Japan

Abstract: Background: The psychological condition and frequency of going out (FGO) of community-dwelling older adults after the spread of COVID-19 will provide insights for supporting the daily lives of community-dwelling older adults. Going out is defined as moving from one’s own home to a place or region beyond one’s own home and is considered to reflect the daily and social life of community-dwelling older adults. This study investigates the relationship between the FGO and current psychological condition after the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Declining trunk muscle strength is caused by long-term inactivity [ 44 ]. It has already been reported that the older adults during the COVID-19 pandemic period decreased their frequency of going out, especially women, and that they were aware of their physical and mental decline due to voluntarily refraining from this activity [ 45 , 46 ]. Even during the COVID-19 pandemic, maintaining social participation is a key strategy for preventing sarcopenia and frailty [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Declining trunk muscle strength is caused by long-term inactivity [ 44 ]. It has already been reported that the older adults during the COVID-19 pandemic period decreased their frequency of going out, especially women, and that they were aware of their physical and mental decline due to voluntarily refraining from this activity [ 45 , 46 ]. Even during the COVID-19 pandemic, maintaining social participation is a key strategy for preventing sarcopenia and frailty [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease (COVID-19) pandemic forced people worldwide to refrain from going outdoors and partake in outdoor activities to prevent the spread of infection. As a result, the elderly in the community were particularly deprived of their important outdoor activity and social interactions in the wake of COVID-19 [1]. In Japan, the infection rate began to soar by the end of March 2020, with an alarming increase in severe infections.…”
Section: Introductionmentioning
confidence: 99%
“…Going outside, referring to movement from one’s own dwelling to a place/location outside one’s own dwelling, reflects older adults’ daily physical activities and social engagements (e.g., taking a walk, working in garden/field, shopping, visiting family/friends, healthcare visit, volunteering, religious service attendance, traveling, or hobby activities) ( Baker et al, 2003 ; Fujita et al, 2006 ; Shimokihara et al, 2022 ). Research has shown multiple benefits of going outside and related physical and social activities for older adults’ physical and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that older adults’ destinations during COVID-19 were predominantly for physical exercise located closer to home. A study of Japanese older adults also found that decreased frequency of going outside due to COVID-19 had detrimental effects on their psychological conditions—mental fatigue, not smiling as much as before, and anxiousness to go outside ( Shimokihara et al, 2022 ). These informative studies show the importance of examining COVID-19’s impact on older adults’ daily lives.…”
Section: Introductionmentioning
confidence: 99%